Instructional leadership: validity and reliability of PIMRS 22-item instrument - Abdul Aziz, Nor Azni; Foo, Say Fooi; Hassan, Aminuddin; Asimiran, Soaib (American-Eurasian Network for Scientific Information, 2014)
Background: Instructional leaders are responsible for organizing, creating, and ensuring a positive attitude toward change. This role is very important for ensuring the success of any reforms. Objective: The main objective of this paper is to establish the validity and reliability of the twenty-two item version of the “Principal Instructional Management Rating Scale” (PIMRS-22) instrument to measure the level of instructional leadership behaviors of principals in implementing the educational policy change of School-Based Assessment (SBA). This twenty-two item instrument was developed by Hallinger (2013) and is based on the Instructional Leadership Model which included three dimensions; determine school mission, management of an instructional program, and creating a learning culture within a school. This instrument was validated by experts and its reliability tested within a pilot study conducted with a total of 60 teachers from 3 secondary schools. Results: The overall reliability coefficient of this instrument was determined to be .94. The determination of school mission had a coefficient of .85, the management of the instructional program .88, and the creation of a learning climate .90. Conclusion: Based on the Cronbach alpha coefficient results, this instrument has content validity, as well as good reliability for quantitatively measuring instructional leadership qualities of principals when implementing educational reform.